Getting It Right in Science and Medicine Can Science Progress through Errors? Fallacies and Facts - Kricheldorf, Hans R.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book advocates the importance and value of errors for the progress of scientific research! Hans Kricheldorf explains that most of the great scientific achievements are based on an iterative process (an 'innate self-healing mechanism'): errors are committed, being checked over and over again, through which finally new findings and knowledge can arise. New ideas are often first confronted with refusal. This is so not only in real life, but also in scientific and medical research. The author outlines in this book how great ideas had to ripen over time before winning recognition and being accepted. The book showcases in an entertaining way, but without schadenfreude, that even some of the most famous discoverers may appear in completely different light, when regarding errors they have committed in their work. This book is divided into two parts. The first part creates a fundament for the discussion and understanding by introducing important concepts, terms and definitions, such as (natural) sciences and scientific research, laws of nature, paradigm shift, and progress (in science). It compares natural sciences with other scientific disciplines, such as historical research or sociology, and examines the question if scientific research can generate knowledge of permanent validity. The second part contains a collection of famous fallacies and errors from medicine, biology, chemistry, physics and geology, and how they were corrected. Readers will be astonished and intrigued what meanders had to be explored in some cases before scientists realized facts, which are today's standard and state-of-the-art of science and technology. This is an entertaining and amusing, but also highly informative book not only for scientists and specialists, but for everybody interested in science, research, their progress, and their history! .
Part I Insights and definitions: Introduction -- What is the meaning of science? -- Laws of nature in everyday life -- Antiscience and antireductionism -- Paradigm change and progress -- How much science is there in medicine? -- Part II From fallacies to facts: Prominent mistakes, and how they were revised: Medicine -- Biology -- Chemistry -- Physics and geology -- Concluding remarks.
Keywords: Chemistry; Physics; Astronomy; Science -- History; Physics -- Philosophy; Science -- Philosophy; Chemistry; Physics and Astronomy; History of Science; Philosophical Foundations of Physics and Astronomy; Philosophy of Science